Optimization of Artificial Insemination Program in Buffalo - Surya Natal Tambing; Mozes R Toelihere; Tuty L Yusuf (Indonesian Center for Animal Research and Development, 2000)
Development of buffalo was relatively slow in the last five years (1993-1997), but the number of slaughtered animals was also increased in the same period. Factors limiting their development were extensive farming system, farming as a secondary enterprise, slow growth and low reproductive efficiency of the animals. Optimization of artificial insemination (AI) program in one of the alternative to improve buffalo productivity in Indonesia. AI is an effective tool toimprove the genetic quality and to increase the buffaloes population. Application of AI in buffalo has been conducted since 1975, but until now the results are not still significant. Within the last four years the calving average was 750 head/year, the implementation of targeted insemination doses reached less than 50%/year with S/C still above 2 and CR 38.32%. The limiting factors affecting this low performance are quality of semen, female fertility, skill of technician and zootechnical knowledge of farmers. Improvement of reproductive efficiency of buffaloes interrelated with optimization of AI program could be imposed through increasing of ability of farmers to detect oestrus, oestrus synchronization using hormones (PGF-2α and progesterone), improvement of quality of frozen semen with special attention on dilution materials used, control of equilibration time, and control of duration and temperature of thawing, as well as accuracy of insemination time. Key words: AI, buffalo, semen quality, optimization, oestrus synchronization